(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This work presents the design, simulation, and practical implementation of a 4-bit R-2R resistor-ladder digital-to-analog converter circuit. The R-2R DAC is a fundamental component in digital signal processing and communication systems, providing a crucial interface between the digital and analog domains. This research investigates the theoretical underpinnings of R-2R DAC architecture, highlighting its binary weighted resistor network and its ability to generate precise analog voltage levels from digital input. A comprehensive analysis of the design parameters, including resistor values and circuit topology, is performed to achieve optimal performance. The work encompasses both theoretical modeling and practical experimentation, with simulations aiding in the verification of the design. The proposed 4-bit R-2R DAC is tested for linearity, accuracy, and dynamic range. Implementation challenges are addressed, and solutions are proposed to ensure the faithful conversion of digital data to analog voltage levels. Furthermore, the influence of resistor tolerances and non-idealities on the DAC’s performance is investigated, and compensation techniques are explored to enhance accuracy. The results of this research demonstrate the successful realization of a 4-bit R-2R DAC, providing precise analog voltage outputs with a fine resolution, thereby contributing to the advancement of digital-to-analog conversion techniques. This work contributes to a better understanding of R-2R DAC technology and offers valuable insights for engineers and researchers working on signal processing, instrumentation, and digital communication systems